Pengaruh Diskon, Promosi, dan Rekomendasi Algoritma Terhadap Perilaku Pembelian Impulsif Makanan Non-Halal pada Aplikasi GoFood di Surabaya - Aurelia Tiffany Hereynzeta; Jessica Angeline Fonda; J. E Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This research seeks to investigate the impact of discount, promotion, and algorithm recommendation on impulsive buying of non-halal food through GoFood application in Surabaya. This research applies a quantitative approach using non-probability sampling with a purposive sampling technique. To be eligible for this study, participants had to meet the following requirements that include customers who have experience purchasing non-halal food through GoFood and actively use the application. Information was gathered via online. A total of 200 participants received and completed the research instrument and the gathered information was processed with the SPSS program. The results indicate that discount, promotion, and algorithm recommendation significantly influence consumers' impulsive buying behavior when purchasing non-halal food through the GoFood application in Surabaya.